Developments of real time and low cost VHF/UHF data acquisition system: article / Erwin Zulkarnain Idris - Idris, Erwin Zulkarnain (2017)
Very High Frequency (VHF)/Ultra High Frequency (UHF) plays a significant and vital role in our daily communications life. Thus, making it crucial to develop a data acquisition system to assist and facilitate further research and studies on VHF/UHF such as in amplitudes variations due to propagations characteristics. Currently, available data acquisition systems are very expensive, complex (non-user friendly), rigid and limited capabilities due to its hardware restrictions/limitations. Consequently, a real-time and low-cost data acquisition system was developed by using microcomputer (Raspberry Pi 3b) and Software Defined Radio (SDR). The system successfully acquired and collected relevant data (frequency amplitudes) that would be resourceful for further analysis and studies of the VHF/UHF signals.